EDUCATIONAL RESOURCES AVAILABILITY AND UTILIZATION AS DETERMINANT OF STUDENTS ACADEMIC PERFORMANCE IN SOUTH WEST NIGERIA - Tunde, Ajiboye (African Journal of Education and Practice, 2022)
Purpose: The aim of the study is to provide educational planners with relevant items of information with respect to the extent of educational resources availability and utilization in public secondary schools as it affects productivity in educational system. Methodology: The descriptive research design of the ex post facto type was adopted for the study. The population of the study comprises all academic staff and three hundred level students in the six (6) selected public Colleges of Education in Southwest Nigeria. Purposive sampling technique was used to select six (6) public Colleges of Education in Southwest Nigeria, three (3) each from State and Federal Colleges of Education. Findings: The study showed that a positive and significant relationship existed between resource situation and students' academic performance in public Colleges of Education in Southwest, Nigeria. It also showed a positive and significant relationship between human and material resource situation and students' academic performance. The findings of this study are consistent with that of Oni (1992), which found that inadequate and unqualified teachers in the school system caused low students' academic performance since adequate and qualified teachers have been found as the drivers of effective educational system. Unique Contribution to Theory, Practice and Policy: The study found that there was positive correlation among material, physical and human resources and students' academic performance in public colleges of Education in Southwest Nigeria, the study thus recommends that government and policy makers in these educational institutions should place emphasis on adequate provision of these germane resources in order to enhance students' academic performance and thus national development. College management in public Colleges of Education in Southwest Nigeria should endeavour to provide enough resources for improvisation, in case the basic physical needs of the institutions could not be adequately met. Parents are admonished to equip their children and wards in public colleges of Education in Southwest Nigeria with the necessary educational needs. Philanthropists, societies, old students association and other organization are admonished to come to the aids of governments in the provision of basic physical and material researches need of public colleges of Education in Southwest Nigeria since it had been established that government alone cannot effectively shoulder the responsibility of educational financing.